2016
DOI: 10.1016/j.jagp.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Treatment on Remission of Late-Life Depression with Venlafaxine and Subsequent Aripiprazole or Placebo Augmentation

Abstract: Objectives Prior treatment history can inform clinical decisions about subsequent treatment choices. We examined the impact of prior antidepressant treatment on outcome of treatment with venlafaxine only and then with augmentation with aripiprazole or placebo in depressed older adults. Methods We analyzed outcome data from a randomized, placebo-controlled clinical trial of aripiprazole augmentation in depressed older adults. The study consisted of an open-label lead-in phase with venlafaxine XR, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…This finding is consistent with our recent report on this same trial (Hsu, in press), which found that when given continuation venlafaxine plus placebo, having a prior history of antidepressant treatment was associated with a lower likelihood of achieving remission; but when adding aripiprazole, having a prior history of antidepressant treatment was not related to differences in remission rates. This prior work did not statistically test whether a prior history of antidepressant treatment moderated the efficacy of aripiprazole vs. placebo.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with our recent report on this same trial (Hsu, in press), which found that when given continuation venlafaxine plus placebo, having a prior history of antidepressant treatment was associated with a lower likelihood of achieving remission; but when adding aripiprazole, having a prior history of antidepressant treatment was not related to differences in remission rates. This prior work did not statistically test whether a prior history of antidepressant treatment moderated the efficacy of aripiprazole vs. placebo.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, benzodiazepines may be cardioprotective, while fluoxetine may have a deleterious effect [ 43 ]. Sertraline, on the other hand failed to improve prognosis of HF [ 44 ], while a beneficial effect of venlafaxine was documented when co-administrated with aripiprazole in patients with end-stage HF [ 45 ]. Finally, in a study of 259 patients with HF and depression, antidepressants were not associated with improved prognosis, despite improvement in symptoms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Κατά αυτό τον τρόπο, οι κατηγορίες των αντιψυχωσικών φαρμάκων φαίνεται να έχουν διαφορετική επίδραση στην πρόγνωση της νόσου: οι βενζοδιαζεπίνες ίσως έχουν προστατευτικό χαρακτήρα (HR: 0.70) για καρδιαγγειακό θάνατο, ενώ η φλουοξετίνη ίσως να έχει επιβλαβή επίδραση (HR: 1.66)[509]. Άλλες φαρμακευτικές ουσίες όπως η σετραλίνη δε φαίνεται να επιδρούν θετικά στην πρόγνωση της ΚΑ[510] ενώ η ευεργετική επίδραση της βενλαφαξίνης τεκμηριώνεται με τη συγχορήγηση αριπιπραζόλης σε ασθενείς με ΚΑ τελικού σταδίου[511]. Πάντως, η εξατομικευμένη και πολυεπίπεδη αντιμετώπιση της κατάθλιψης στην ΚΑ είναι πολύ σημαντική για την πρόγνωση της νόσου αλλά και για την ανακούφιση των ασθενών, ειδικά εκείνου που βρίσκονται στα τελικά στάδια ή πάσχουν και από σύνδρομο καχεξίας[356].Πέρα από την φαρμακευτική αγωγή, άλλες πολυδιάστατες πρακτικές φαίνεται να παίζουν σημαντικό ρόλο στην θεραπεία της κατάθλιψης και να έχουν τεκμηριωμένα θετική επίδραση στην πρόγνωση της ΚΑ.…”
unclassified